2020
DOI: 10.1177/1367493520925661
|View full text |Cite
|
Sign up to set email alerts
|

The emotional and psychiatric problems of adolescents on parole whose parents are substance users: A Brazilian cross-sectional study

Abstract: The aim of this study is to evaluate the associations between having parents with substance use problems, and having suffered neglect within the family, and behavioral problems (psychological and drug use) among adolescents. All the participants were enrolled on the socio-educational parole scheme, ‘Assisted Freedom’. In this cross-sectional study, 150 adolescents were interviewed using the Drug Abuse Screening Test, Teen Addiction Severity Index, and Childhood Trauma Questionnaire. Ninety-five percent of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Parentification includes situations where children have to take on adult roles and responsibilities, even at the expense of their education, and this can harm children's well-being. Children who experience parentification experience severe psychological distress, excessive stress and have a higher risk of developing mental disorders, as research has shown by Perruci et al (2021) and Chase (1999) that the effects of parentification in childhood can have a long-term impact.…”
Section: Parentification As a Form Of A Child's Strugglementioning
confidence: 99%
See 1 more Smart Citation
“…Parentification includes situations where children have to take on adult roles and responsibilities, even at the expense of their education, and this can harm children's well-being. Children who experience parentification experience severe psychological distress, excessive stress and have a higher risk of developing mental disorders, as research has shown by Perruci et al (2021) and Chase (1999) that the effects of parentification in childhood can have a long-term impact.…”
Section: Parentification As a Form Of A Child's Strugglementioning
confidence: 99%
“…Drug abuse is a global and public health-related issue in many countries, impacting individuals, families, and communities (Dyba et al, 2019;Freisthler et al, 2017b;Perruci et al, 2021;Khalidass et al, 2021). In Indonesia, the threat of drugs has been considered an extraordinary crime (BNN Republik Indonesia, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Drug abuse is a social issue of global concern, and an increase in the number of drug abusers has placed a serious burden of disease on individuals, families and society ( Kepple, 2017 ; Perruci et al, 2021 ). According to statistics, approximately 279 million people worldwide used drugs in 2020, representing a 22% increase from the number of drug users in 2010 ( UNODC, 2021 ).…”
Section: Introductionmentioning
confidence: 99%